2010
DOI: 10.1002/elan.200904685
|View full text |Cite
|
Sign up to set email alerts
|

Electochemiluminescence of CdTe/CdS Quantum Dots with Triproprylamine as Coreactant in Aqueous Solution at a Lower Potential and Its Application for Highly Sensitive and Selective Detection of Cu2+

Abstract: Anodic electrochemiluminescence (ECL) of 3-mercaptopropionic acid (MPA)-capped CdTe/CdS core-shell quantum dots (QDs) with tripropylamine (TPrA) as the co-reactant were studied in aqueous (Tris buffer) solution for the first time. The results suggest that the oxidation of TPrA at a glassy carbon electrode (GCE) surface participated in the ECL of QDs, and the onset potential and the intensity of ECL of CdTe/CdS QDs were affected seriously by TPrA, as the co-reactant, in Tris buffer solution. The onset potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…It has been reported that the ECL emission based on Cd-based semiconductors can be quenched statically by Cu 2+ . 28,29 In this work, to our best knowledge, the effective ECL quenching of the g-C 3 N 4 /GO system by trace amounts of Cu 2+ has never been reported before, demonstrating its potential application in Cu 2+ detecting. samples are directly added into 5 mL ECL cell for ECL measurement respectively.…”
Section: Condition Optimizationmentioning
confidence: 89%
“…It has been reported that the ECL emission based on Cd-based semiconductors can be quenched statically by Cu 2+ . 28,29 In this work, to our best knowledge, the effective ECL quenching of the g-C 3 N 4 /GO system by trace amounts of Cu 2+ has never been reported before, demonstrating its potential application in Cu 2+ detecting. samples are directly added into 5 mL ECL cell for ECL measurement respectively.…”
Section: Condition Optimizationmentioning
confidence: 89%
“…ECL reactions can be classified into oxidative-reduction and reductive-oxidation, according to the generated intermediate species being reducing or oxidizing during an electrochemical process. In general, commonly-used ECL coreactants include oxalate (C 2 O 4 2-) [15], tri-n-propylamine (TPrA) [20], dibutylaminoethanol (DBAE) [21], and sulfite (SO 3 2-) [22], which belong to the ''oxidation-reduction'' reaction mechanism, and hydrogen-peroxide [24], and peroxydisulfate (S 2 O 8 2-) [25], which are "reductiveoxidative" coreactants. Table 1 shows the corresponding mechanisms of the "oxidation-reduction" reaction.…”
Section: Coreactant Eclmentioning
confidence: 99%
“…Embedded ECL reagents owning high affinity with dsDNA, Ru(phen) 3 2+ and Ru‐dppz, have been also employed to develop label‐free ECL sensors for Hg 2+ . Except for Pb 2+ and Hg 2+ , other heavy metal ions (Cu 2+ and Ag + ) were assayed using ECL FNA‐based sensors. In addition, the researchers also developed ECL sensors for simultaneous detection of multi metal ions…”
Section: The Application Of Ecl Fna‐based Sensors In Food Contaminantsmentioning
confidence: 99%